Sleep spindle alterations in patients with Parkinson's disease - Christensen, Julie A. E.; Nikolic, Miki; Warby, Simon C.; Koch, Henriette; Zoetmulder, Marielle; Frandsen, Rune; Moghadam, Keivan K.; Sorensen, Helge B. D.; Mignot, Emmanuel; Jennum, Poul J. (Frontiers in Human Neuroscience, 2015)
The aim of this study was to identify changes of sleep spindles (SS) in the EEG of patients with Parkinson’s disease (PD). Five sleep experts manually identified SS at a central scalp location (C3-A2) in 15 PD and 15 age- and sex-matched control subjects. Each SS was given a confidence score, and by using a group consensus rule, 901 SS were identified and characterized by their 1) duration, 2) oscillation frequency, 3) maximum peak-to-peak amplitude, 4) percent-to-peak amplitude and 5) density. Between-group comparisons were made for all SS characteristics computed, and significant changes for PD patients versus control subjects were found for duration, oscillation frequency, maximum peak-to-peak amplitude and density. Specifically, SS density was lower, duration was longer, oscillation frequency slower and maximum peak-to-peak amplitude higher in patients versus controls. We also computed inter-expert reliability in SS scoring and found a significantly lower reliability in scoring definite SS in patients when compared to controls. How neurodegeneration in PD could influence SS characteristics is discussed. We also note that the SS morphological changes observed here may affect automatic detection of SS in patients with PD or other neurodegenerative disorders.